A based-on-set-partitioning exact approach to multi-trip of picking up and delivering customers to airport. (2018) - Sun, Wei; Yu, Yang; Li, Jia
Picking up and delivering customers to airports (PDCA) is a new service provided in China. The multi-trip mode of PDCA (MTM-PDCA) service is a promising measure to reduce operation costs. To obtain the exact solution, we propose a novel modelling approach including two stages. In the first stage, all feasible trips of each subset of the customer point set are produced, and then the two local optimum trips of each subset can be obtained easily. Subsequently, using the local optimum trips obtained in the first stage, we establish the novel trip-oriented set-partitioning (TO-SP) model to formulate MTM-PDCA. The MTM-PDCA based on the TO-SP model can be solved exactly by CPLEX. By testing extensive instances, we summarise several managerial insights that can be used to successfully reduce the costs of PDCA by using multi-trip mode.